YOUTH DEVELOPMENTS AND INNOVATIONS IN REM HEAD TREPANATION. (THIS WORK IS DEDICATED TO THE DEVELOPMENT OF TREPANATION METHODS FOR STUDENTS USING THE EXAMPLE OF A RAM HEAD). (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The subject of neurosurgery has been improved over the years and is provided with high-tech equipment, and therefore the number of students, residents and young scientists interested in the field of neurosurgery is growing. In the formation of practical skills, it is important to study them step by step; the role of simulation equipment and animal models is important in this. The choice of experimental animal in different countries depends on economic, geographical and religious worldviews.